THE CORRELATION BETWEEN INTERNET ADDICTION AND MENTAL DISORDERS: A LITERATURE REVIEW (CIPEEX, 2025)
Introduction: Since the advent of the internet, people started to use it through multiple ways and gradually it became a technological tool used without discrimination, which lead us to, as we know now, the Internet Addiction (IA). However, this addiction affects not only adults and adolescents, but also children which can bring them a lot of consequences. Objective: this study aimed to understand the correlation between the IA and mental disorders in children, through a literature review. Methodology: Throughout a search on the databases of National Library of Medicine (PubMed) and MedLine, using the search terms of “Internet Addiction”, “Children”, “Mental disorders” and the logical operator “AND” we chose four articles, written in the last five years, in English and free to access. Results: It was possible to correlate the IA with mental disorders in children. We observed a higher risk of emotional, behavior and social issues in kids that use the internet without discrimination. Furthermore, we could understand the influence of this addiction to suicidality, maily in male participants. Moreover, the impact of internet abuse in the physical well-being, sleep durability and quality, physical activities and obesity, musculature pain, ocular health and headaches. Conclusion: Therefore, it is actually important to link internet abuse with mental disorders in children among consequences that extend beyond just mental ones. Nevertheless, because of the lack of research about this theme, specially in children, we arent able neither to be highly detailed about this matter, nor to plan preventive strategies for the internet addiction in kids – which we hope that, in a close future, we will be able to do, given the increasing need of a perspective towards this age group.
Keywords: children; mental disorders; internet addiction